The Influence of Organizational Climate on Employee’s Job Satisfaction in the Higher Education Sector in UAE: The Case of a Private Local University - Shaya, Nisrine; AbuKhait, Dr Rawan (IJRDO - Journal of Social Science and Humanities Research, 2016)
The 21 st century marked severe challenges and difficulties (i.e. the influence of globalization, security-related issues, the revolution in the information technology, etc.) facing organizations, that are not unique to a particular industry or organization, regardless their size and structure (Castro & Martins 2010). Looking at the organization itself the “the body of a successful organism behaves as a whole system” (Kretiman & Morrman 1997), where the wise body would not place its parts in opposition or conflict with each other. On the contrary, “the appropriate specialization of body parts, operating in coordination and cooperation” (1997), is the key for the organization survival. In fact, for the organization to be capable of facing the challenges and difficulties imposed by the current era, it has to acknowledge the importance of the human capital. The people in the organization are the essential source of intelligence, flexibility and responsiveness, and hence supportive climate, preserving their cooperative endeavors, should be created. Due to these reasons and more organizational climate and job satisfaction continues to capture the attention of researchers and managers, due to their strong influence on the success of the organizations. Researchers have long focused on improving the work climate, as means of increasing job satisfaction (Jyoti 2013). It is reported that “if jobs or work environment are developed to provide a more desirable work environment, an increase in job satisfaction will result” (p. 66). And, in return “satisfied and full-energy personnel are the most important source of organization” (Dizagh et al. 2012). Job performance and efficiency in getting the work done will reflect the level of satisfaction of that; hence, organizational climate and job satisfaction are critical factors to improve effectiveness.